Hospitality in Luke's gospel, and implications for contemporary living - Nguyen, Duyen Thi My (The Australasian Catholic record, 2022)
What Is Hospitality? 'Hospitality' comes from the Latin 'hospitalitas', meaning 'friendliness to guests'. 'Host' comes from the Latin `Hospes', which gives rise to the terms, 'hospitality, 'hospitable', `hospitaller', 'hospital', 'hospice', 'hostel' and 'hotel'. Hospitality thus involves the care, protection and good treatment by one person (a host) toward another (a guest) in a safe and comfortable atmosphere.